2001
DOI: 10.1038/35081051
|View full text |Cite
|
Sign up to set email alerts
|

Proteorhodopsin phototrophy in the ocean

Abstract: Proteorhodopsin, a retinal-containing integral membrane protein that functions as a light-driven proton pump, was discovered in the genome of an uncultivated marine bacterium; however, the prevalence, expression and genetic variability of this protein in native marine microbial populations remain unknown. Here we report that photoactive proteorhodopsin is present in oceanic surface waters. We also provide evidence of an extensive family of globally distributed proteorhodopsin variants. The protein pigments com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
494
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 720 publications
(504 citation statements)
references
References 21 publications
9
494
1
Order By: Relevance
“…The PR gene fragments fell into several families not restricted to the PR groups previously reported using non-degenerate PCR primers (Béjà et al, 2001;Sabehi et al, 2003) and the overall diversity of the PR sequences was comparable to that previously detected in the Sargasso Sea metagenome (Venter et al, 2004). No apparent bias was also observed regarding any potential preference of our primers toward low G þ C amplicons (Suzuki and Giovannoni, 1996) (Supplementary Figure S2), further supporting the adequacy of these primers to sample across different subpopulation of the PR family.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PR gene fragments fell into several families not restricted to the PR groups previously reported using non-degenerate PCR primers (Béjà et al, 2001;Sabehi et al, 2003) and the overall diversity of the PR sequences was comparable to that previously detected in the Sargasso Sea metagenome (Venter et al, 2004). No apparent bias was also observed regarding any potential preference of our primers toward low G þ C amplicons (Suzuki and Giovannoni, 1996) (Supplementary Figure S2), further supporting the adequacy of these primers to sample across different subpopulation of the PR family.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental sequences are represented by blue or green bands corresponding to their predicted absorption maxima to illustrate their distribution in different depths and seasons. The two subfamilies previously reported to be spectrally tuned (Béjà et al, 2001) are marked in blue and green boxes. SAR86 and SAR11 PR families, as well as few different PR representative's names from the Pacific Ocean (Béjà et al, 2001), Sargasso Sea shotgun-sequencing project (Venter et al, 2004), Mediterranean Sea bacterial artificial chromosomes (BACs) (Sabehi et al, , 2005, Pelagibacter ubique (Giovannoni et al, 2005a) and marine Archaea (Frigaard et al, 2006) are indicated to serve as orientation marks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations